Mentoring the educational leader : a practical framework for success - Strike, Kimberly T., 1966- (Rowman & Littlefield Education, 2011)
This book provides short, pertinent content relevant to everyday events within a school. Based on theory and experience, the practical application is directly aligned to administrative duties, and chapters can be read as needed. The format allows the administrator to read the content, apply the information through completion of a follow-up activity, and record one's reflection which serves as a foundation for discussions with one's mentor. An administrative evaluation instrument is provided so readers canreview administrative standards and self-assess strengths and weaknesses.